Nationally representative surveys show gradual shifting of overweight and obesity towards poor and less-educated women of reproductive age in Nepal - Sutradhar, Ipsita; Akter, Tahmina; Hasan, Mehedi; Das Gupta, Rajat; Joshi, Hemraj; Haider, Mohammad Rifat; Sarker, Malabika (Journal of biosocial science, 2021)
Overweight and obesity are considered major public health concerns all over the world. They have the potential to increase the risk of developing non-communicable diseases in reproductive age women, increasing their risk of pregnancy related complications and adverse birth outcome. This study was carried out to identify the trend of prevalence of overweight and obesity, along with their determinants, among reproductive age women (15-49 years) in Nepal. Data were taken from the nationally representative 2006, 2011 and 2016 Nepal Demographic and Health Surveys (NDHSs). Women were considered to be overweight or obese when their BMI was 23.0-27.5 kg/m(2) or >= 27.5 kg/m(2), respectively. Univariate, bivariate and multivariate analyses were performed, with significance taken at p<0.05. The prevalences of overweight and obesity both showed rising trends in women of reproductive age in Nepal from 2006 to 2016, particularly among those with no education, only primary education and poor women. The presence of overweight and obesity was found to be significantly associated with the sample women's age, educational status, wealth index, place of residence, ecological zone, developmental region, number of household members, marital status and ethnicity. In 2016 one in every three women of reproductive age in Nepal was either overweight or obese. As overweight and obesity have detrimental effects on women's health, the Government of Nepal, in collaboration with other government and non-government organizations, should take action to halt the rising trends in overweight and obesity in the country.
Gesehen am 18.08.2021
First published: 27 March 2020